Proceedings of the 2nd International Conference Postgraduate School 2018
DOI: 10.5220/0007546705450549
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Count and Differential Leukocyte Count of Carp (Cyprinus carpio Linn) after Infected by Aeromonas salmonicida

Abstract: The hematology examination be able to descript the health of fish. The aim of this research was to study leukocyte and differential counting leukocyte in Carp (Cyprinus carpio Linn) after infected by Aeromonas salmonicida. P0 was a control group, not infected with Aeromonas salmonicida. P1, P2, and P3 group was infected by Aeromonas salmonicida through different doses, 10 5 cell/ml, 10 6 cell/ml, 10 7 cell/ml. Three days after infection, blood samples were obtained from Punctie Vena Caudal which deposited into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The delayed peak (at 14 days) in the bath challenge suggested that adaptive immune response took longer to develop in the bath route. An increase in leukocytes after bacterial infections was observed in other fish species [30,[58][59][60], which is consistent with our finding after infection with M. viscosa (Figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…The delayed peak (at 14 days) in the bath challenge suggested that adaptive immune response took longer to develop in the bath route. An increase in leukocytes after bacterial infections was observed in other fish species [30,[58][59][60], which is consistent with our finding after infection with M. viscosa (Figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding to positive control, similar results of leucocytosis were recorded after bacterial infection in Tilapia in order to tackle the infection (Mazrouh et al, 2015) which, may be attributed to lymphocytosis and neutrophilia. As well Afiyanti et al (2018) estimated the leukocytes and D.L.C in carp 3 days after A. salmonicida infection and found a significant leukocytosis, eosinophilia, neutrophilia, lymphocytosis and monocytosis and non-significant basophilic count. In treated groups the extract was capable of enhancing the act of the immune system by generating more leucocytes, as a result giving the fish more ability to restrain the bacterial growth in the fish body.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that monocytes also have important functions in cytokine production ( Secombes 1991 ). Afiyanti et al . (2018) proposed that increased numbers of monocytes were associated with bacterial infection.…”
Section: Discussionmentioning
confidence: 99%